If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(2x + 1) + -2ln(x) = 2 Reorder the terms: ln(1 + 2x) + -2ln(x) = 2 (1 * ln + 2x * ln) + -2ln(x) = 2 (1ln + 2lnx) + -2ln(x) = 2 Multiply ln * x 1ln + 2lnx + -2lnx = 2 Combine like terms: 2lnx + -2lnx = 0 1ln + 0 = 2 1ln = 2 Solving 1ln = 2 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Divide each side by '1n'. l = 2n-1 Simplifying l = 2n-1
| 6n+3n=90 | | -7m+21-5(m-1)=8m-(4m-3)-9m+2 | | 7/x+2=4/2x-3 | | x^2+x-3.25=0 | | 3.6+y=1 | | 4/5k-5=-7+2/3k | | x-2-6x=4 | | -[8z-(11z+9)]=9+(2z+3) | | 4m^3-10m^2= | | -2p-6(3-2p)=6(p-3)-16 | | 5x+10=-20fory | | 3x(x-2)+5(x-2)=0 | | 38x-38=38x-38 | | -8(4b+4)+(33b-9)=0 | | 5x+6(x-11)=5(x-12) | | -2=t-3s | | 62+(6x)+(6x+6)=180 | | 16s^2+72s+18=0 | | 12(-82x+26)=84(2x+62) | | 5/3x=56 | | x+5/3=56 | | 4c^2-36c=0 | | 9(3x+6)+(x+2)=11 | | 2n(8n+1)=0 | | 9x+90+y=180 | | x(-5x+2)=24 | | -3u-w=u+7w | | 4x+8+5x-7=180 | | 12+6x=42 | | 6=t+7s | | 6(t-3)+6t=4(3t+5)-12 | | 5x-9x+8=-2+6 |